Strategies for Improving Chinese Writing Exercises of Senior Grade Students in the Primary School of the Yi Ethnic Group - Zhang, Jian; Yu, Mengyue; Abbas, Safdar (Journal of Education, Health and Sport, 2022)
There has been a strong consensus among previous researchers that first language interferes with second language acquisition. A limited number of studies have been conducted to examine this interference in writing Chinese. Chinese writing exercises for primary school students of the Yi ethnic group in rural areas tend to encourage students to incorporate their native language habits into Chinese writing practices. This enables students to apply modern Chinese word order to the Yi language paradigm. Consequently, they are prone to grammatical errors, word order errors, and collocation errors in their compositions. This study focuses on elementary school students' writing abilities in order to alleviate their fears associated with Chinese writing. It also assists them in grasping the second language writing paradigm, and enjoying writing. In addition, by analyzing the composition errors of the students in the corpus, we propose some practical recommendations from three perspectives: educators, students, and institutions. These recommendations will enhance language and writing education within ethnic communities through theoretical and practical strategies.